Atenolol Versus Propranolol in The Treatment of Infantile Hemangioma: A Randomized Controlled Trial (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Propranolol, a nonselective beta-blocker is recommended for the treatment of Infantile Hemangiomas (IHs). However, this treatment is not risk-free and it cannot be applied to many patients because of respiratory comorbidities. Atenolol is a cardioselective beta-blocker and recently, some studies have reported their experience in using oral Atenolol in IHs. The aim of this study was to compare the outcome of Atenolol versus Propranolol in the treatment of IHs. Materials and methods: This randomized controlled trial was carried out in the Department of Pediatric Surgery of Chittagong Medical College Hospital from January 2020 to December 2020. 49 patients aged less than 7 years with a diagnosis of cutaneous IH were randomly assigned into two groups. Group A received oral Propranolol (2 mg/kg/day) and Group B received oral Atenolol (1 mg/kg/day). Follow-up was made at 1 month, 3 months and 6 months. Main outcome measures were changes in Hemangioma Activity Score (HAS) and adverse effects. 5 patients did not show up in any follow-up. Finally, a total of 44 patients (22 in Propranolol group and 22 in Atenolol group) were included in the analysis.Results: There was no significant difference in age and sex between the groups. Mean age was 7.5 months in Group A and 11.5 months in Group B (p= 0.580). Pretreatment HAS was similar between groups (median 4.0 in Group A, 4.4 in Group B, p=0.208) and posttreatment HAS was also similar between two groups (median 1 in Group A, 0 in Group B, p=0.243). In Group A median hemangioma size reduced from 3.30 cm to 0.55 cm and from 3.28 cm to 0.76 cm in Group B, significantly size reduced in both groups (p=